التنظيم الدستوري والتشريعي لحق المشاركة السياسية - شبر، رافع خضر صالح; فاضل، سامر حسين; العنزي، علاء عبدالحسن كريم (جامعة بابل - كلية القانون, 2021)
عندما اعتمدت الدول مبدأ الاقتراع العام أو الشامل فأنها بذلك قد منحت حق التصويت لأكبر عدد من المواطنين فلا توجد دولة تمنح هذا الحق لجميع مواطنيها بحكم كونهم مواطنين بل نجد أن تشريعات الدول الخاصة بالانتخابات تحرم بعض فئات الشعب من ممارسة حق التصويت ويعد هذا أمرا طبيعياً لأن الاقتراع العام بالمفهوم المطلق يحمل بذاته تناقضاً وعدم منطقية لأنه سيمنح حق الانتخاب على سبيل المثال للقاصرين والمجانين لذلك كان تدخل المشرع أمرا ضرورياً لتلطيف مفهوم الاقتراع الشامل، فالاقتراع العام يعني إعطاء اختيار ممثلي الشعب لجميع المواطنين من كلا الجنسين والبالغين سناً معينة ولا يستثنى من ممارسة هذا الحق أي فرد بسبب تعليمه أو ولادته أو وضعه الاقتصادي، إلا أن عمومية الاقتراع هذه يتوقف تطبيقها على موقف المشرعين بحيث يمكن أن تخضع لشروط عدة، منها موضوعية وهي شرط السن والجنسية والأهلية ومنها شكلية (إجرائية) وهي شرط القيد في سجلات الناخبين وشرط الإقامة.
When states adopted of universal or universal suffrage, they have thus granted the right to vote to the largest number of citizens. There is no state that grants this right to all of its citizens by virtue of being citizens. Rather, we find that the legislation of states regarding elections prohibits some groups of people from exercising the right to vote, and this is a natural matter because voting The general concept, in absolute terms, carries a contradiction and irrationality in itself, because it will grant the right to vote, for example, to minors and insane. Therefore, the intervention of the legislator was necessary to soften the concept of universal suffrage. General voting means giving the choice of representatives of the people to all citizens of both sexes and adults. A certain age is not excluded from the exercise of this right by any individual due to his education, birth or economic status, except that this general suffrage depends on the position of legislators so that it can be subject to several condition, including objectivity, which is a condition of age, nationality, and eligibility, including formality (procedural), which is the condition of registration in the voter register and residency condition .
Keywords: التنظيم الدستوري -- التنظيم التشريعي -- المشاركة السياسية -- الانتخابات التشريعية -- السلطة السياسية